POLITISASI HIJAB KONTESTASI PEMILIHAN KEPALA DAERAH - Nurul Azizah; Mohammad Armoyu (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
This research about the transformation of hijab women candidates in the political stage direct election of the regional head (Pilkada). In Indonesia hijab experienced a transformative instrument motif. This is related to the dynamics of democratization in Indonesia, the factor of political identity and religious polarization is very strong. The focus of this study is the motive of wearing a hijab on women's candidates influenced various aspects including religion, fashion trend, even political interests to gain power. The theoretical study uses the rational action theory approach is the front stage and backstage. The object of this research is women candidates who suddenly use the hijab before the election of the regional head. The purpose of this study to determine the motives behind the use of hijab, the objective of political parties to bring women candidates wearing hijab to gain sympathy and captivate the voice of Muslim voters. The research method is a textual analysis on the use of Hijab. The results are expected with the emergence of women candidates who have hijab in direct local elections (Pilkada) bringing blessings and benefits, not just playing masks on the political stage as a means of winning and power for personal and group interests.